Tinctoride A, a New Hopan-Type Triterpenoic Peracid from the Thallus of Lichen Parmotrema Tinctorum (Despr. ex Nyl.) Hale - Le-Thuy-Thuy-Trang Hoang; Thanh-Nha Tran; Thi-Phi-Giao Vo; Hoang-Vinh-Truong Phan; Phan-Si-Nguyen Dong; Dinh-Tri Mai; Ngoc-An Nguyen; Thi-Minh-Suong Huynh; Hong Truong Luu; Tien-Dung Le; Minh-Trung Dao; Van-Kieu Nguyen (Journal of Chemistry)
A new hopan-type triterpenoic peracid, tinctoride A (1), together with three known compounds, zeorin (2), 6β,22-dihydroxyhopane (3), and ergosterol peroxide (4), was isolated from Parmotrema tinctorum (Despr. ex Nyl.) Hale. Their chemical structures were identified by extensive 1D and 2D NMR analysis and high-resolution mass spectroscopy and compared with those reported in the literature. The enzyme inhibitory potential of compounds 1–3 against α-glucosidase was investigated, exhibiting nil to weak inhibitory activity.